Behavioural and demographic characteristics of attenders at two genitourinary medicine clinics in England. Issue 6 (December 1997) - Catchpole, M; Connor, N; Brady, A; Kinghorn, G; Mercey, D; Band, B; Thin, N
Abstract : OBJECTIVES: To investigate how attenders with sexually transmitted disease (STD) differ from the general population with respect to sexual behaviour, and to identify which attenders at genitourinary medicine (GUM) clinics are at particular behavioural risk for acquiring STD. DESIGN: Multicentre cross sectional survey. SETTING: Two genitourinary medicine clinics, one in London and one in Sheffield SUBJECTS: 20, 516 patients attending the two clinics over an 18 month period. MAIN OUTCOME MEASURES: Behavioural and demographic characteristics and clinical diagnoses were recorded for each patient. RESULTS: 8862 patients, in whom 12, 506 diagnoses were made, were seen in the Sheffield clinic, and 11, 654 patients, in whom 20, 243 diagnoses were made, were seen in the London clinic. When compared with the reported results from a general population survey, there were higher proportions of clinic attenders reporting two or more sexual partners in the preceding 12 months (p < 0.001), and a higher proportion of males reporting homosexual contact (13% compared with 1%, p < 0.001). Only age and number of sexual partners in the past 12 months were significantly associated with acute STDs for each sex in each clinic. Acute STDs tended to occur with greater frequency in the younger age groups, peaking among 16-19 year olds, particularly among females. CONCLUSIONS: The results have confirmed that patients with STDs exhibit higher risk sexual behaviour than the general population, and have highlighted the problem of continuing high risk behaviour among younger attenders, particularly younger homosexual men. This study has demonstrated that among GUM clinic attenders age and number of sexual partners are key risk factors for the acquisition of an acute STD. The results of this survey also indicate, however, that half of the females and more than one quarter of males with acute STDs reported only one sexual partner in the past 12 months, suggesting that health education messages should point out that it is not only those who have multiple recent sexual partners, or who have recently changed sexual partner, that are at risk of STD, including HIV.